Spontaneous Abortion and Failure of Human Cytotrophoblasts to adopt a vascular adhesion phenotype - Al-Obaidi, Asmaa’ Bauer; Hussain, Alaa Gina; Shamran, Haider Ahmed (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Differentiating cytotrophoblasts transform their adhesion receptor phonotype so as to resemble the endothelial cells they replace a process that is required for normal placentation, and any defect in this adhesion phenotype switch might lead to pregnancy failure. Patients and Methods: Curate samples of the materno-fetal interface were taken from 20 women with spontaneous first trimester abortion and 6 control women undergone elective termination of pregnancy in the first trimester. Immunohistochemistry analysis of paraffin embedded sections of these curate samples was performed using monoclonal antibodies for cytokeratin, PECAM-1 and VCAM-1. Results: Cytokeratin showed positive immunostaing of the cytotrophoblasts lining the blood vessels, and PECAM-1 was positive in the cytotrophoblasts in only two cases who had elective termination of their pregnancy, while VCAM-1 immunostaining of the cytotrophoblasts was positive in three cases that had elective termination of pregnancy and only two cases that had spontaneous abortion. Conclusion: Defective expression of endothelial cell adhesion molecules in human cytotrophoblasts might predispose to abnormal placentation, pregnancy failure and subsequent abortion.